Greek thinkers: a history of ancient philosophy - Gomperz, Theodor (J. Murray, 1901)
CONTENTS.-Vol.1. Book 1. The beginnings. Book 2. From metaphysics to positive science. Book 3. The age of enlightenment.-vol. 2. Book 4. Socrates and the Socratics. Book 5. Plato.-vol. 3. Book 5 (continued) Plato.-vol. 4. Book 5. Aristotle and his successors.